Luminescent Bis-Cyclometallated Iridium(Iii) Complexes Containing Phosphine-Based Ligands: Influence of the P^N Bridge - Moya-Duran, S; Moya-Duran, S (Elsevier Ltd, 2015)
Three cationic bis-cyclometallated iridium complexes [Ir(CN-ppyMe)2(PN)][PF6](1-3) with 4-methyl-2-phenylpyridine (ppyMe) as the CN-cyclometallated ligands and 8-(diphenylphosphino)quinoline (Ph2Pqn, L1), 2-(diphenylphosphinoamino)pyridine (Ph2PNHpy, L2) or 2-(diphenylphosphinoamino) pyrimidine (Ph2PNHpym, L3) as PN-ligands, were prepared, and their crystal structures and photoluminescence were investigated. The substitution of an "aromatic CAr" (of a quinolyl group) by an "NH" bridge between the phosphine and imine ligating units of the PN ligand dramatically changes the luminescence characteristics of the resulting complexes. The complexes 2-3 featuring the P-NH-N ligand emit in the blue region, whereas complex 1 incorporating the P-CAr-N unit displays orange photoluminescence. © 2014 Elsevier Ltd. All rights reserved.